Wear resistance, oil resistance, morphology and vulcanization performances of ethylene-vinyl acetate/acrylonitrile butadiene rubber composites - B. C. Wang; H. He; X. F. He; H. D. Chen; B. Huang (eXPRESS Polymer Letters, 2019)
The composites consisting of ethylene-vinyl acetate rubber (EVM) and acrylonitrile butadiene rubber (NBR) were prepared by two-step blending method, and were reinforced with carbon black (CB) using 1,4-bis(tert-butylperoxyisopropyl) benzene (BIPB) as crosslinking agent. In addition, wear and oil resistance, morphology, vulcanization and dynamic mechanical properties of the composites were systematically investigated. 3D graph was used to analyze the trend of wear and oil resistance of the composites. SEM images showed that the wear mechanism of the composites was mainly abrasive wear, accompanied by fatigue wear. With the increase of NBR content, the wear resistance was effectively improved, which was revealed by the DIN abrasion volume, worn surfaces morphology and roughness. Meanwhile, the oil resistance was also improved according to the rate of volume change and surface contact angle. The EVM/NBR composites prepared by the two-step blending method showed higher ΔH (maximum torque MH – minimum torque ML) than pristine EVM or NBR did. The composites containing 30 phr of CB exhibited excellent wear and oil resistance, which broadened the applications field of the EVM/NBR composites.